The Contribution of Complementary and Alternative Medicine to Reduce Antibiotic Use: A Narrative Review of Health Concepts, Prevention, and Treatment Strategies. (3rd February 2019) - Baars, Erik W.; Zoen, Eefje Belt-van; Breitkreuz, Thomas; Martin, David; Matthes, Harald; Schoen-Angerer, Tido von; Soldner, Georg; Vagedes, Jan; Wietmarschen, Herman van; Patijn, Olga; Willcox, Merlin; Flotow, Paschen von; et al.
Abstract : Aim. The aim of this narrative review was to explore the potential contributions of CAM to reduce antibiotic use. Methods. We searched PubMed, Embase, and Cochrane Database of Systematic Reviews with a specific, limited set of search terms and collected input from a group of expert CAM researchers to answer the question: What is known about the contribution of CAM health and health promotion concepts, infection prevention, and infection treatment strategies to reduce antibiotic use? Results. The worldview-related CAM health concepts enable health promotion oriented infection prevention and treatment aimed at strengthening or supporting the self-regulating ability of the human organism to cope with diseases. There is some evidence that the CAM concepts of health (promotion) are in agreement with current conceptualization of health and that doctors who practice both CAM and conventional medicine prescribe less antibiotics, although selection bias of the presented studies cannot be ruled out. There is some evidence that prevention and some treatment strategies are effective and safe. Many CAM treatment strategies are promising but overall lack high quality evidence. Conclusions. CAM prevention and treatment strategies may contribute to reducing antibiotic use, but more rigorous research is necessary to provide high quality evidence of (cost-)effectiveness.